Acute stress enhances the glutamatergic transmission onto basoamygdala neurons embedded in distinct microcircuits. Issue 1 (December 2017) - Song, Chen; Zhang, Wen-Hua; Wang, Xue-Hui; Zhang, Jun-Yu; Tian, Xiao-Li; Yin, Xiao-Ping; Pan, Bing-Xing
Abstract Amygdala activation is known to be critical for the processing of stressful events in brain. Recent studies have shown that the projection neurons (PNs) in amygdala, although architecturally intermingled, are integrated into distinct microcircuits and thus play divergent roles in amygdala-related behaviors. It remains unknown how stress regulates the individual amygdala PNs embedded in distinct microcircuits. Here, by using retrograde tracing and electrophysiological recording in in vitro slices, we explored the modulation of acute immobilization stress (AIS) on the basoamygdala (BA) PNs projecting either to medial prefrontal cortex (mPFC) or elsewhere, which we designated as BA-mPFC and non-BA-mPFC PNs respectively. The results showed that in the control mice, both the excitatory and inhibitory postsynaptic currents (sEPSCs/sIPSCs) were comparable between these two subsets of BA PNs. The influences of AIS on sEPSCs and sIPSCs were overall similar between the two neuronal populations. It markedly increased the sEPSCs amplitude but left unaltered their frequency as well as the sIPSCs amplitude and frequency. Despite this, several differences emerged between the effects of AIS on the distribution of sEPSCs/sIPSCs frequency in these two groups of BA PNs. Similar changes were also observed in the sEPSCs/sIPSCs of the two PN populations from mice experiencing forced swimming stress. Their intrinsic excitability, on the other hand, was nearly unaltered following AIS. Our results thus suggest that acute stress recruit both BA-mPFC and non-BA-mPFC PNs mainly through enhancing the glutamatergic transmission they receive.